Eleições presidenciais de 2021 em São Tomé e Príncipe: “Povo põe, Povo tira”, “povo tira, povo põe”1 - Nascimento, Augusto (The Journal of US Africa -Studies, 2023)
Based on the 2021 presidential elections in São Tomé and Príncipe, this text focuses on the political confrontation in the archipelago, largely determined by the long-term strategy of Patrice Trovoada, head of ADI, a politician far from the land but decisively influential as none other, including those of the MLSTP, the independence party. The description and analysis of electoral processes show how programmatic and doctrinal contents have long been abandoned in favor of adherence to political solutions focused on personalities, object of adhesion or rejection expressed in elections. This happened in the recent presidential elections that, permeated by political and legal litigation, dragged on from the end of July to the beginning of September 2021. The results of successive elections are the episodic and volatile expression of the desire for political solutions of a more democratic or more authoritarian nature. Regardless of the promises of respect for democracy and the law, it is possible that the vox populi supports an authoritarian governance that asserts itself guided by the intention to instill order, which appears as a requirement for the desired economic growth and wealth. Keywords: Democracy, authoritarianism, elections, São Tomé and Príncipe. 1. Este texto começou a ser escrito após a primeira volta das presidenciais de 2021. Foi concluído após a segunda volta em inícios de outubro de 2021. Ao tempo, Patrice Trovoada, chefe do ADI, primeiro-ministro entre 2014 e 2018, vivia fora do arquipélago. O governo, da Nova Maioria, resultava de uma coligação do MLSTP e do PCD. Em 2022, o partido ADI obteve outra maioria absoluta de deputados. Logo, Patrice Trovoada regressou ao país. Após a sua posse como primeiro-ministro, a pretexto de um dito golpe de estado, em 25 de novembro assassinaram-se pessoas no quartel de São Tomé. Este facto decerto feriu a expetativa de parte dos ilhéus relativamente à governação de Patrice Trovoada (nota de A. Nascimento).